Molecular Virology of Hepatitis E Virus - Holla, R. Prasida; Ahmad, Imran; Ahmad, Zulfazal; Jameel, Shahid (Seminars in Liver Disease, 2013)
Hepatitis E virus (HEV) is the causative agent of hepatitis E. It is a nonenveloped virus with a ∼7.2 kilobases positive-stranded RNA genome. The molecular virology of HEV is getting better understood with the development of replicons and in vitro infection systems, and the discovery of related viruses that infect animal species other than humans. This review focuses on the virology of HEV and updates the current knowledge on the HEV genome and its constituent proteins—ORF1, ORF2, and ORF3, and the viral life cycle.
Keywords: hepatitis E; HEV; ORF1; ORF2; ORF3; RNA replication